SPACE RESOURCES: A NEW BALANCE OF INTERESTS FOR THE 21ST CENTURY - Erices Bravo, Álvaro Andrés (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: the Art. II of the 1967 Outer Space Treaty (OST), which prohibits national appropriation by claim of sovereignty, use or occupation, is a jus cogens norm and has become a guarantee of peace in space, as well as the basis of international space law. In opposition, the creation of national legislations that allow the appropriation of space resources to their citizens, the advance of the private sector in space activities all over the world, the initiative to create the International Lunar Research Station (ILRS), and The Artemis Accords, put the interpretation of this fundamental principle under debate. In the 21st century, the proliferation of new space missions of public-private nature has created feasible commercial opportunities, such as space mining. All of this has deepened the debate within the United Nations Committee on the Peaceful Uses of Outer Space (UNCOPUOS) on the need (or not) for elaborate new legal definitions and a legal regime for space resources. For this, it’s necessary to generate a unified interpretation by the States based on the "balance of interests" principle. Research methods: study of specialized bibliography and national and international legislations, observation methods and analysis of information related to space activities. Results: in this article it will be evaluated whether it’s possible to establish a new global legal interpretation of Art. II of the OST of 1967 to allow the harmonization of private and public interests. Discussion: the Artemis Accords, the ILRS and the national legislations of States that currently allow their citizens to appropriate space resources are, in fact and in practice, the spearhead of NewSpace and their main characteristic is that they are initiatives carried out outside UNCOPUOS. What would happen if soon, in a hypothetical case, The Artemis Accords and the ILRS project were to have more than a hundred signatory States in total?